IDENTIFYING THE ABILITY OF STUDENTS IN TRANSLATING LITERARY WORK - Farida Repelita Waty Kembaren; Arya Wiranda; Rahma Yani; T. Khoirunnisa. YL (LPPM Universitas Cipta Mandiri, 2024)
This study explores the competence of fifth-semester English Education Program students in translating literary works, notably poetry, from English to Indonesian. The research utilizes a quantitative method, combining a test and a closed-response questionnaire to measure translation skills and identify prevalent issues. The data suggest that 38.46% of students display adequate translation competence, with just 2.56% obtaining an exceptional level. Common issues include determining word meanings, utilizing the correct tenses, choosing acceptable words, and using conjunctions. These findings underline the need for specific instructional assistance to develop students' translation abilities, especially in addressing the complexity of literary translation. The research emphasizes the necessity of establishing linguistic and cultural competency in translation education, highlighting the function of vocabulary, grammar, and knowledge of poetic elements. By addressing these areas, instructors may better help students obtain more significant levels of translation competence, boosting their overall language ability and cultural awareness.